Դարաշամբի 1590 թ. օսմանյան հարկացուցակը - Միրզաբեկյան, Գեորգի (Մատենադարան)
According to the Ottoman Extended Tax Register of the Yerevan Vilayet of 1590, the Ottoman authorities incorporated Darashamb into the administrative unit of Nakhijevan. The Ottoman tax register of Darashamb’s region is a very important source from the aspect of demography and socio-economic issues. It gives a good possibility to study the ethnic composition of the region, toponyms, number of villages, collected taxes etc. In 1590, Darashamb consisted of three villages: Dibkend, Bashkend and Ortakend located south of the city of Nakhijevan, on the right side of the Araks River. The study of the Ottoman tax register shows that the population of the villages was exclusively Armenian and it consisted of 54 families. According to this primary source of 1590, the inhabitants were mainly engaged in agriculture. Especially popular were wheat, barley and cotton, the cultivation of which contributed to the socio-economic well-being of Darashamb. It should be emphasized that the three villages of Darashamb had practically the same level of development in terms of demographic and economic components. По данным османского расширенного реестра Ереванского вилайета 1590 г., османские власти включили Дарашамб в административную единицу Нахичевани. Османский налоговый реестр Дарашамбского района – очень важный источник для исследования демографических и социально-политических характеристик региона. Перепись содержит данные о его этническом составе, топонимике, количестве сел, взимаемых налогах и т. д. В 1590 г. Дара- шамб состоял из трех сел: Дибкенд, Башкенд и Ортакенд, которые располагались южнее города Нахичевань, на правом берегу реки Аракс. Изучение налогового реестра показывает, что население сел составляли исключительно армяне – всего 54 семьи. Согласно первоисточнику, в 1590 г. жители в основном занимались сельским хозяйством – преимущественно пшеницей, ячменем и хлопком, выращивание которых способствовало социально-экономическому благополучию Дарашамба. Три села Дарашамба имели практически одинаковый уровень развития с точки зрения демографической и экономической составляющих.
Keywords: Պատմաբանասիրություն